2010
DOI: 10.1002/aic.12433
|View full text |Cite
|
Sign up to set email alerts
|

Separation of small organic ions from salts by ion‐exchange membrane in electrodialysis

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Electrodialysis (ED) can be applied in the food and fermentation industry for separating inorganic salts and organic ions from other fractions. However, the separation efficiency for small organic ions should be understood in detail. In this article, the membrane selectivity and transport mechanism of small organic ions from mixed salts by ion-exchange membranes are theoretically and experimentally investigated. First of all, the influence of current density on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 33 publications
3
29
0
1
Order By: Relevance
“…Similar results were found by Kabsch-Korbutowicz et al [9] -the ED process with monoselective anion-exchange membranes enabled better regeneration of spent brines contaminated by NOM, than standard ED. Detailed investigation of electrodialytic fractionation of small organic ions from mineral salts revealed that the process efficiency was influenced by current density, organic ion size and charge, as well as by the type of functional groups fixed to organic particles [10]. It is interesting to note that the big organic ions (of molecular weight above 130 kDa) can be deposited at the membrane surface, thus creating an additional bipolar layer and alternating the membrane selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Kabsch-Korbutowicz et al [9] -the ED process with monoselective anion-exchange membranes enabled better regeneration of spent brines contaminated by NOM, than standard ED. Detailed investigation of electrodialytic fractionation of small organic ions from mineral salts revealed that the process efficiency was influenced by current density, organic ion size and charge, as well as by the type of functional groups fixed to organic particles [10]. It is interesting to note that the big organic ions (of molecular weight above 130 kDa) can be deposited at the membrane surface, thus creating an additional bipolar layer and alternating the membrane selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Los procesos de electro diálisis presentan un amplio espectro de aplicación desde la industria de alimentos, de reciclaje hasta la generación de energía [9][10][11][12][13][14][15][16][17] . Estos procesos se basan en el transporte másico selectivo de iones a través de membranas de intercambio iónico bajo la acción de un campo eléc-trico externo.…”
Section: Introductionunclassified
“…Their work builds from Zhang et al (2012) in which a 'selectrodialysis' process is innovated with the specific purpose of separating monovalent and multivalent anions, as well as Zhang et al (2011b) in which the separation of small organic ions from salts was investigated.…”
Section: Nutrient Recovery Using Electrodialysismentioning
confidence: 99%
“…Their study also identified that osmosis and electro-osmosis can limit the concentration of nutrients in the product. Zhang et al (2011b) demonstrated that it is possible to neglect these effects in relatively low concentration processes using synthetic wastewater.…”
Section: Osmosis and Electro-osmosismentioning
confidence: 99%
See 1 more Smart Citation